The boy on Fairfield Street : how Ted Geisel grew up to become Dr. Seuss - Krull, Kathleen (Random House, 2004)
Introduces the life of renowned children's author and illustrator Ted Geisel, popularly known as Dr. Seuss, focusing on his childhood and youth in Springfield, Massachusetts.